Mengenal Muhammad Abu Zahrah Sebagai Mufassir - Muhammad Badrun (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2011)
In the history of interpretation of the Qur’an we find that the study ofQur’anic interpretation started from the time of the Messenger of Allah untilthe present time. From the period in which the commentary is learned andstudied through the riwayat (narration) and talqin (indoctrination) from a teacherto his student until the time when every person ‘feel’ to have the authority tointerpret the verses of the Qur’an. The study of Qur’anic intepretation hasundergone the tremendous growth in the fourth phase of the compilationperiod (tadwin). That was the phase in which the interpretation of the Qur’anwass controlled by the interpretation based on reason and the opinion of theinterpreter (mufassir); interpretations coloured by various sects and schools ofthought. The development of this kind of interpretation, although believed tobe a logical consequence of the development history of science, but then notnecessarily be accepted by the ulamas and received positive appreciation of them.Like Muhammad Husein adh Dhahabi, Muhammad Abu Zahrah, and so forth.For Imam Muhammad Abu Zahrah (1898-1974/1315-1394) theinterpretation of the Quran which is based on a variety of goals and interestsas well as a variety of comprehension and thinking like that, in fact was oftenaway from the substance of Al-Quran; obscure its miracle power, destroyingthe real meaning and even provide commentary on the sometimes contradictorywith the fundamentals of Islamic teaching. This is awakening his awareness andencourage him to try to straighten out and provide an alternative of moreactual interpretation. So he finally wrote a book of tafsir named “Zahratu alTafasir”. This interpretation is different from the books of the previous tafsirbooks. At least, he did not want to simply follow the tradition (taqlid), themethod or the way used by previous mufassir.